Physiological determinants of individual variation in sensitivity to an organophosphate pesticide in Nile tilapia Oreochromis niloticus - McKenzie, David J.; Blasco, Felipe R. [UNESP]; Belão, Thiago C. [UNESP]; Killen, Shaun S.; Martins, Nathan D. [UNESP]; Taylor, Edwin W.; Rantin, F. Tadeu (Elsevier, 2017)
Individual variation in sub-lethal sensitivity to the organophosphate pesticide trichlorfon was investigated in Nile tilapia, using critical swimming speed (Ucrit) as an indicator. Tilapia exposed for 96 h to 500 μg l−1 trichlorfon at 26 °C (Tcfn group, n = 27) showed a significant decline in mean Ucrit, compared to their own control (pre-exposure) performance in clean water (−14.5 ± 2.3%, mean ± SEM), but also compared to a Sham group (n = 10) maintained for 96 h in clean water. Individuals varied in their relative sensitivity to the pesticide, with the decline in Ucrit after exposure varying from 1 to 41%. The Ucrit of the Tcfn group did not recover completely after 96 h in clean water, remaining 9.4 ± 3.2% below their own control performance. The decline in performance was associated with a significant increase in net cost of aerobic swimming, of +28.4 ± 6.5% at a sustained speed of 2 bodylengths s−1, which translated into a significant decline in swimming efficiency (Eswim) of −17.6 ± 4.0% at that speed. Within the Tcfn group, individual Eswim was a strong positive determinant of individual Ucrit across all trials, and a strong negative determinant of individual% decline in Ucrit after pesticide exposure (P < 0.001, linear mixed effect models). Trichlorfon had no effects on standard metabolic rate or active metabolic rate (AMR) but, nonetheless, individual Ucrit in all trials, and% decline in Ucrit after exposure, were strongly associated with individual AMR (positively and negatively, respectively, P < 0.001). Individual Ucrit under control conditions was also a strong positive determinant of Ucrit after trichlorfon exposure (P < 0.001), but not of the% decline in Ucrit performance. In conclusion, the OP pesticide impaired Ucrit performance by reducing Eswim but individual tilapia varied widely in their relative sensitivity. Intrinsic individual physiology determined effects of the pesticide on performance and, in particular, good swimmers remained better swimmers after exposure.
Keywords: Critical swimming speed; Individual variation; Metabolic rate; Nile tilapia; Respirometry; Trichlorfon